Studying Hammer horror - Walden, Victoria Grace (Leighton Buzzard : Auteur, 2016)
Intended for students, fans, and general readers, this book transcends superficial preconceptions of Hammer horror in order to reach the essence of Hammer.
JSTOR
Keywords: Hammer Film Productions; Hammer Film Productions; Horror films -- History and criticism; Films d'horreur -- Histoire et critique; Horror films; Criticism, interpretation, etc